Secondary School Learners' Self-Efficacy and Achievement in Non-Routine Mathematics Problem-Solving - Munyaradzi Chirove (Indonesia Approach Education, 2023)
This paper uses a correlational research design to investigate the predictive power of the sources of self-efficacy and non-routine problem-solving achievement. The data were collected from a sample of 118 high-achieving secondary school learners in the Gauteng province, South Africa, using questionnaires, a problem-solving test, and interviews. Their self-efficacy beliefs were categorized into mastery experience, vicarious experience, social persuasion, and physiological state. The findings revealed that the physiological state, vicarious experience, and mastery experience self-efficacy beliefs positively impacted problem-solving achievement, while that of social persuasion was negative. The magnitudes of the impact of the physiological state and social persuasion sources of self-efficacy were relatively greater than the others. Each source of self-efficacy was discovered to have an insignificant, weak, positive linear relationship with problem-solving achievement.